Chondrostereum purpureum as an inundative biological control agent for invasive woody weeds in New Zealand - Ramsfield, T.D.; Carlson, C.A.; Power, M.W.P.; Skudder, D. (New Zealand Plant Protection, 2010)
Chondrostereum purpureum is a basidiomycete fungus that is being investigated as an inundative biological control agent for invasive woody weeds This study was conducted to assess the susceptibility of seven species of weeds to C purpureum The species that were inoculated in this trial were broom (Cytisus scoparius) gorse (Ulex europeaus) buddleia (Buddleja davidii) Himalayan honeysuckle (Leycesteria formosa) hawthorne (Crataegus monogyna) poplar (Populus trichocarpa) and willow (Salix matsudana) Two isolates of C purpureum and a control were used and were each replicated 12 times All plants were potted and the trial took place under nursery conditions Mortality and canker size were measured 6 months after inoculation Data were analysed using SAS The highest mortality (50) was recorded for broom with one isolate but very little mortality was observed across the other species A highly significant weed by isolate interaction was observed with regards to lesion length with weed species susceptibility varying with respect to one of the C purpureum isolates Hawthorn and willow had greater lesion lengths after inoculation with the same isolate that had caused mortality in broom The results from this trial are being used to direct a larger field trial